Definition Of Disturbance Rejection Requirements For Improved Vibrational Ride Comfort - Burkhardt, T.; Ozkurt, S.; Fichter, W. (My University, 2024)
In manned aviation, the improvement of the ride comfort becomes increasingly important. The phenomena that cause discomfort during flight are divided into two types. The first is the whole-body vibration mainly introduced through the high-frequency rotation of the rotor. The second type of discomfort is kinetosis. Passengers who experience kinetosis can suffer from disorientation, nausea and vomiting. It is initiated by low-frequency oscillations below 0.5 Hz. These are mainly caused by the reaction to disturbances from the pilot or the automatic flight control system. The severity of kinetosis can be mitigated with a proper controller design. However, no metric exists to take the kinetosis effect into account at the controller design. Nevertheless, there are already models to describe the development of kinetosis depending on the flight maneuvers. These models are either too simplified to depict the complex processes or are nonlinear and therefore cannot be taken into account in linear control. One of these nonlinear models is already adapted to the helicopter environment. It predicts the intensity of kinetosis depending on occurring translational and rotational movements. This paper describes the systematic analysis of this model resulting in new disturbance rejection bandwidths of the flight control system that ensure a reduction of kinetosis. The model is linearized and its characteristics are analyzed and compared to the nonlinear model. Based on the transfer functions of the linearized model, new requirements for the disturbance rejection bandwidths are identified. These requirements are stricter and can therefore serve as an extension of the ADS-33 requirements. Controllers that are designed to meet the new disturbance rejection bandwidths result in a kinetosis reduction of more than 20 % compared to controllers that comply with the bandwidths of ADS-33. This shows that the new requirements result in a significant reduction of kinetosis enabling a smooth ride in passenger transport.